WHEN DEATH MEETS LIFE: Exploring the Links Between Migration and Salvation - Cruz, Gemma Tulud (Asian Horizons, 2012)
Mobility is as old as the human species. It is very much a part of human existence such that it is regarded as an engine of human history. Today, however, we are witnessing human mobility in unprecedented ways. At no other point in history has the number of people on the move at such a large scale that the current historical period is being referred to as the age of migration.1 To be sure, this claim is not without merit. The report by the International Organization for Migration (IOM), for instance, says that the number of people living outside their country of origin has dramatically increased from 150 million in 2000 - when IOM published its first World Migration Report — to more than 214 million in 2010. That’s an increase of 64 million in a matter of 10 years. Moreover, the IOM reports that the figure could rise to as much as 405 million by 2050.2 Worldwide, migrants now account for approximately 3.1% of the world population and more than 10 percent of the population in 38 countries. In fact if all migrants in the world were to come together to constitute a country, theirs would be the world’s fifth most populous